Analisis Sistem Pengendalian Intern Persediaan Barang Dagangan Pada Minimarket Alfamart Poligon Di Palembang - Hilwa Anggraini; Zein Ghozali; Masnoni; Nelly; Sri Sutandi (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of the study was to determine the implementation of an internal control system for merchandise inventory at the Alfamart Poligon Minimarket in Palembang. The data analysis method used is qualitative analysis, namely explaining the theories in reference books related to research. The data used in this study is primary data. The benefit for the Alfamart Poligon Minimarket in Palembang is as input for the management that is useful for improving company policies on controlling merchandise inventory. The results of this study indicate that the application of an internal control system for merchandise inventory at the Alfamart Poligon Minimarket in Palembang is not good enough because there is still no warehouse function so that there is a dual task between the store head function and the warehouse function as well as the sales clerk function. The stock of name, which is carried out twice a year, can cause a loss of merchandise inventory in the Minimarket so that the company's assets are reduced which is the main asset of the Alfamart Poligon Minimarket in Palembang.